Resilient business strategies in the German hospitality industry and its viability - Tonia Ruppenthal; Jana Rückert-John (Tourism & Management Studies)
This study aimed to investigate the German hospitality industry to find out which resilient business strategies operational managers applied during the COVID-19 pandemic and which are considered viable for the future. Drawing on a multiple case study approach, semi-structured online expert interviews were conducted with twelve operational managers from certain sectors of the German hospitality industry. A manual qualitative content analysis was applied to analyse data and to identify resilient business strategies for the COVID-19 pandemic through an iterative coding process. The study results show that operational managers applied diverse resilient business strategies within six areas: grocery shopping, food processing and menu planning, work environment and workplace, guest and customer world, marketing and sales concepts and under prospective perspectives. The business strategies are resilient, as operational managers responded to the crisis in a situation- and organisation-specific manner and implemented transformative business activities. This study provides valuable insights for organisations, managers and practitioners in the different hospitality industry sectors by identifying resilient business strategies in times of crisis. It also highlights what business strategies are considered viable for the future, which could thus serve as a blueprint for the hospitality industry.